PEMAHAMAN KEBERAGAMAAN DAN GERAKAN KELOMPOK FPI SURABAYA - Ma’arif, Syamsul (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2012)
Attitudes ofÂ FPIÂ (Islamic Defenders Front) inÂ IndonesiaÂ so far Â impressed 'frontal' and againstÂ any form ofÂ indecent behavior.Â Their action, in factÂ it can be saidÂ as one of theÂ deepestÂ expressionÂ ofÂ a group ofÂ MuslimsÂ in articulatingÂ religious teachingsÂ areÂ embraced, or as an attitude of